On the incidental exposure of the general public to invasive forest pests through mainstream media - Bastien CASTAGNEYROL; Benno A. AUGUSTINUS; Zina DEVETAK; Tugba DOGAN; Tiia DRENKHAN-MAATEN; Renata GAGIĆ-SERDAR; Eva GROZNIK; Milica GRUBAČ; Andrija JUKIĆ; Milena LAKICEVIC; Liva LEGZDINA; Miia MÄNTTÄRI; et al. (Urban Forestry & Urban Greening, 2026)

Exposure and magnification of PFAS in a temperate estuarine food web, including top predators - Martine J. van den Heuvel-Greve; Jildou Schotanus; Michiel J.J. Kotterman; Christiaan J.A.F. Kwadijk; Sophie M.J.M. Brasseur; Mardik Leopold; Jetze van Zwol; Douwe van den Ende; Suzanne A. Cornelisse; Evert de Froe; Edwin M. Foekema (Marine Pollution Bulletin, 2026)

Spatial habitat partitioning enables coexistence of three Gobiidae species in estuarine environments - Phumza M. Ndaleni; Josie South; Leopold A. J. Nagelkerke; Olaf L. F. Weyl; Phakama Nodo; Nicola C. James (Journal of Fish Biology, 2026)
This study examines resource partitioning (feeding morphology, diet and habitat partitioning) among three gobiid species, the Knysna sandgoby Psammogobius knysnaensis , the prison goby Caffrogobius gilchristi and the river goby Glossogobius callidus , within an estuarine environment. The findings revealed distinct habitat preferences: P. knysnaensis predominantly occupied the sandy mouth of the estuary, C. gilchristi favoured the lower reaches and G. callidus was abundant in the upper reaches. Principal component analysis of feeding morphological traits indicated significant overlap between the feeding morphology of C. gilchristi and G. callidus . Although the two species showed overlapping morphological traits, they exhibited distinct diets, influenced by differences in prey availability within their feeding environments. Cyclopoids, which were widespread throughout the estuary, were a common dietary item for both species. Psammogobius knysnaensis and C. gilchristi had overlapping diets, but each species appeared to dominate in different habitats. This study highlights that habitat partitioning drives resource partitioning among the three species, enabling their coexistence in a dynamic estuarine ecosystem.

Trophic niche partitioning during ontogeny in three skate species, Raja brachyura, Raja clavata, and Raja montagui, in the Northeast Atlantic - Eleanor S.I. Greenway; Ailynn Swiers; Jurgen Batsleer; Paddy A. Walker; Hendrik V. Winter; Leopold A.J. Nagelkerke; Jan Jaap Poos (Estuarine, Coastal and Shelf Science, 2025)

Weathering by mycorrhizal fungi defines a threshold for nutrients in ecosystems along an aridity gradient - Doreen Fleck; Simon Thiedau; Diana Boy; Leopold Sauheitl; Svenja Stock; Moritz Köster; Ralf Oeser; Michaela A. Dippold; Sandra Spielvogel; Yakov Kuzyakov; Yosef Steinberger; Roberto Godoy; et al. (Science of The Total Environment, 2025)

Decomposition of a minke whale carcass in a temperate dune ecosystem - Martin J. Baptist; Mardik F. Leopold; Marinka E. B. van Puijenbroek; Hans Verdaat; Nicole Janinhoff-Verdaat; Dennis R. Lammertsma; Wim J. Dimmers; Paul F. A. M. Römkens; Jan Burgers (Frontiers in Marine Science, 2025)
Due to the benefits to the ecosystem there is a growing incentive to limit management interventions of stranded whales. This study was conducted to test the impact of a stranded whale carcass decomposing in a natural dune ecosystem and to gain experience in managing a beached whale carcass. A 4.70 m male juvenile minke whale Balaenoptera acutorostrata carcass washed up on the western side of the uninhabited island Rottumerplaat, the Netherlands. The carcass was moved the same night into the dunes to prevent it from washing back into the sea. Regular field visits were undertaken and wildlife trail cameras were placed to document the decomposition stages and the attraction of avifauna. Pitfall traps were placed to monitor insect fauna next to the carcass. Vegetation plots were surveyed to document changes to the dune vegetation and soil cores were taken to determine the increase in metal, carbon and nutrient contents. Decomposition of the carcass until the bare skeleton within the temperate dune ecosystem took about two years. The carcass was highly beneficial for beetle biodiversity, attracting different beetle species at various stages of decomposition. In total, 129 species of beetles were found near the carcass, of which eight species are specific for carcasses. For scavenging birds such as gulls, magpies and carrion crows the skin of the minke whale was too tough to break open. While the initial nutrient leakage from the carcass was toxic to dune plants immediately around the carcass, it eventually promoted lush vegetation growth due to increased fertility. The bioavailable metal contents in the soil for potassium (K) and nickel (Ni) showed a significant increase due to the presence of the whale carcass up to six months. Significantly increased levels of arsenic (As), cobalt (Co) and vanadium (V) were found up to one and a half years later and sodium (Na) and manganese (Mn) persisted in elevated levels up to two years later. Recommendations were given on management interventions when leaving a whale carcass on site.

Land use change and forest management affect soil carbon stocks in the central hardwoods, U.S. - Lucas E. Nave; Kendall DeLyser; Grant M. Domke; Scott M. Holub; John M. Kabrick; Adrienne B. Keller; Patricia Leopold; Matthew P. Peters; Kevin A. Solarik; Christopher W. Swanston (Geoderma Regional, 2025)

Ontogenetic shifts by juvenile fishes highlight the need for habitat heterogeneity and connectivity in river restoration - Twan Stoffers; Anthonie D. Buijse; Jan Jaap Poos; Johan A. J. Verreth; Leopold A. J. Nagelkerke (Limnology and Oceanography, 2025)
Large‐scale anthropogenic river modifications have caused the loss of critical floodplain nursery habitats for riverine fish, leading to population declines. Restoration efforts have been implemented to recover these habitats, but with varying success. Understanding how larval and juvenile fish use habitats in dynamic river environments is essential for improving restoration strategies. We assessed ontogenetic shifts in habitat use by young‐of‐the‐year fishes in the lower Rhine, analyzing 2167 samples across 18 restored floodplains over three growing seasons (2018–2020). Five distinct nursery habitats were identified: (1) exposed, fast‐flowing habitats with coarse substrate; (2) turbid, nonflowing areas with high turbidity and chlorophyll; (3) shallow, vegetated habitats with macrophytes and shoreline vegetation; (4) deeper, sheltered habitats with structural complexity; and (5) shallow, slow‐flowing areas. Habitat use shifted significantly with ontogeny across species. Larvae generally preferred shallow habitats ( 50‐cm depth), favoring fast‐flowing areas (e.g., asp, barbel, ide), or deeper, nonflowing habitats (e.g., bream, zander). Our findings thus highlight the critical importance of habitat heterogeneity and connectivity for riverine fish biodiversity. Restoration strategies should prioritize the creation of a mosaic of shallow, low‐velocity habitats for larvae, alongside deeper, fast‐flowing, or sheltered areas for juveniles. Additionally, the movement of rheophilic species from floodplain habitats to the main river channel emphasizes the need for maintaining continuous connectivity between floodplains and the river.

The Main Geohazards in the Russian Sector of the Arctic Ocean - Artem A. Krylov; Daria D. Rukavishnikova; Mikhail A. Novikov; Boris V. Baranov; Igor P. Medvedev; Sergey A. Kovachev; Leopold I. Lobkovsky; Igor P. Semiletov (Journal of Marine Science and Engineering, 2024)
The Arctic region, including vast shelf zones, has enormous resource and transport potential and is currently key to Russia’s strategic development. This region is promising and attractive for the intensification of global economic activity. When developing this region, it is very important to avoid emergency situations that could result in numerous negative environmental and socio-economic consequences. Therefore, when designing and constructing critical infrastructure facilities in the Arctic, it is necessary to conduct high-quality studies of potential geohazards. This paper reviews and summarizes the scattered information on the main geohazards in the Russian sector of the Arctic Ocean, such as earthquakes, underwater landslides, tsunamis, and focused fluid discharges (gas seeps), and discusses patterns of their spatial distribution and possible relationships with the geodynamic setting of the Arctic region. The study revealed that the main patterns of the mutual distribution of the main geohazards of the Russian sector of the Arctic seas are determined by both the modern geodynamic situation in the region and the history of the geodynamic evolution of the Arctic, namely the formation of the spreading axis and deep-sea basins of the Arctic Ocean. The high probability of the influence of seismotectonic activity on the state of subsea permafrost and massive methane release is emphasized. This review contributes toward better understanding and progress in the zoning of seismic and other geological hazards in the vast Arctic seas of Russia.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Continuous measurement of CO2, CH4 and H2O fluxes from a restored marl fen and inland salt marsh communities overlaying a Solvay waste settling basin - Timothy Morin; Veronica Davies-Taylor; Timothy A. Volk; Anthony Eallonardo; Donald J. Leopold (Ecological Engineering, 2024)

The environmental perspective on biomass co-firing operations at coal-fired power plants in the Banten region, Indonesia: a life cycle approach - Irhan Febijanto; Rosmeika Rosmeika; Nadirah Nadirah; Ahmad Ismed Yanuar; Adolf Leopold Sihombing; I. Made Agus Dharma Susila; Hismiaty Bahua; Inna Zulfa Kurniawati; Arief Barkah; Arif Dwi Santoso; Rudi Herdioso; Bambang Rustianto; et al. (Energy, Ecology and Environment, 2024)

A wetland condition assessment to consider ecological relationships of a Maya cultural keystone species within the Lake Atitlan, Guatemala littoral zone - Jorge Garcia-Polo; Stewart A. W. Diemont; Tomasz B. Falkowski; Donald J. Leopold (Wetlands, 2024)

Features of Seismological Observations in the Arctic Seas - Artem A. Krylov; Mikhail A. Novikov; Sergey A. Kovachev; Konstantin A. Roginskiy; Dmitry A. Ilinsky; Oleg Yu. Ganzha; Vladimir N. Ivanov; Georgy K. Timashkevich; Olga S. Samylina; Leopold I. Lobkovsky; Igor P. Semiletov (Journal of Marine Science and Engineering, 2023)
This paper is devoted to the features of seismological observations in the Arctic seas, which are complicated by harsh climatic conditions, the presence of ice cover, stamukhi and icebergs, and limited navigation. Despite the high risk of losing expensive equipment, the deployment of local networks of bottom seismographs or stations installed on ice is still necessary for studying the seismotectonic characteristics and geodynamic processes of the region under consideration, the deep structure of the crust and upper mantle, seismic hazards, and other marine geohazards. Various types of seismic stations used for long-term and short-term deployments in the Russian sector of the Arctic Ocean, as well as various schemes and workflows for their deployment/recovery, are described. The characteristics of seafloor seismic noise and their features are also considered. The results of deployments demonstrate that the characteristics of the stations make it possible to reliably record earthquake signals and seismic noise. Based on the experience gained, it was concluded that the preferred schemes for deploying ocean-bottom seismographs are those in which their subsequent recovery does not depend on their power resources. Usually, such schemes allow for the possibility of dismantling stations via trawling and are suitable for the shelf depths of the sea. The advantages of such schemes include the possibility of installing additional hydrophysical and hydrobiological equipment. When using pop-up ocean-bottom seismographs, special attention should be paid to the careful planning of the recovery because its success depends on the possibility of a passage to the deployment site, which is not always possible due to changing meteorological and ice conditions. Seismic records obtained on the seafloor are characterized by a high noise level, especially during periods of time when there is no ice cover. Therefore, it is recommended to install bottom stations for periods of time when ice cover is present. The frequency range of the prevailing noise significantly overlaps with the frequency range of earthquake signals that must be taken into account when processing bottom seismic records.

Estuarine-Specific Migration of Glass Eels in the Ems Estuary - Jeroen B. J. Huisman; Henry J. Kuipers; Leopold A. J. Nagelkerke; Peter Paul Schollema; Inge van der Knaap (Fishes, 2023)
Understanding recruitment of glass eels in estuaries is crucial for the conservation of the European eel (Anguilla anguilla). However, basic knowledge on estuarine-specific glass eel migration, including in estuarine harbours, is mostly lacking. Therefore, we studied glass eel migration in the Dutch–German Ems estuary and the harbour at Delfzijl (The Netherlands) and tagged glass eels with Visual Implant Elastomer tags (VIE tags). We released 2000 tagged glass eels into the Ems estuary itself and 1000 tagged glass eels into the tidal harbour at Delfzijl. At three estuarine locations, i.e., Delfzijl–Duurswold, Termunterzijl, and Nieuwe Statenzijl, glass eel collectors were strategically placed, each location being progressively situated further upstream in the Ems estuary. Most glass eels (nuntagged = 97,089, ntagged = 74) were caught at Nieuwe Statenzijl, although this location is much further upstream. Lower numbers of glass eels (nuntagged = 1856, n tagged = 31) were caught at Delfzijl–Duurswold and Termunterzijl (nuntagged = 1192, ntagged = 7). Glass eels arrived approximately a week earlier at Nieuwe Statenzijl than at the other two locations, and the migration speed of tagged glass eels was highest at Nieuwe Statenzijl (>2 km/day) and lower (

Contribution of soil bacteria to the atmosphere across biomes - Stephen D.J. Archer; Kevin C. Lee; Tancredi Caruso; Antonio Alcami; Jonathan G. Araya; S. Craig Cary; Don A. Cowan; Claudia Etchebehere; Batdelger Gantsetseg; Benito Gomez-Silva; Sean Hartery; Ian D. Hogg; et al. (Science of The Total Environment, 2023)

Lorenzetti Showers - A general-purpose framework for supporting signal reconstruction and triggering with calorimeters - M.V. Araújo; M. Begalli; W.S. Freund; G.I. Gonçalves; M. Khandoga; B. Laforge; A. Leopold; J.L. Marin; B.S-M. Peralva; J.V.F. Pinto; M.S. Santos; J.M. Seixas; et al. (Computer Physics Communications, 2023)

Correction to: Historical reconstruction of sturgeon (Acipenser spp.) spatiotemporal distribution and causes for their decline in North-Western Europe - Niels W. P. Brevé; Leopold A. J. Nagelkerke; Anthonie D. Buijse; Theodorus J. van Tuijn; AlberTinka J. Murk; Hendrik V. Winter; H. J. Rob Lenders (Biodiversity and Conservation, 2022)

The effects of nest location and beach environment on hatching success for leatherback (Dermochelys coriacea) and green (Chelonia mydas) sea turtles on Bioko Island, Equatorial Guinea - Callie A. Veelenturf; Elizabeth M. Sinclair; Peter Leopold; Frank V. Paladino; Shaya Honarvar (Marine Biology, 2022)

Historical reconstruction of sturgeon (Acipenser spp.) spatiotemporal distribution and causes for their decline in North-Western Europe - Niels W. P. Brevé; Leopold A. J. Nagelkerke; Anthonie D. Buijse; Theodorus J. van Tuijn; AlberTinka J. Murk; Hendrik V. Winter; H. J. Rob Lenders (Biodiversity and Conservation, 2022)
This study aims to reconstruct the historical spatiotemporal distribution of the anadromous sturgeons, Acipenser sturio and A. oxyrinchus, in NW-Europe (especially in the Rhine, Meuse, Scheldt, and Ems rivers, and in the North Sea), in light of evaluating the possibilities for their reintroduction. It is based on fisheries data from the 14th–twentieth century, consisting of > 5000 records of sturgeon landings and sales (c. 40,000 specimens) from the Netherlands, Belgium, Germany, Luxemburg, France and Switzerland. Most data originate from fisheries in the Rhine-Meuse delta (c. 28,000 specimens, 98% of the Rhine catches). Further upstream, far fewer sturgeons (c. 600 specimens) were reported from the Rhine’s mainstem and its principal tributaries, Mosel, Neckar and Main. Smaller tributaries and the Ems, Meuse, and Scheldt rivers seldom yielded sturgeons. This spatial pattern can be related to the species’ preference for large-river habitat, combined with fisheries activities that were most intensive in the delta areas. Sturgeon catches began to dwindle in the late nineteenth century, at a time when river engineering first strongly affected the sturgeon’s reproductive habitats in the Lower Rhine and delta areas. Also from then onwards, North Sea fishery pressure increased, as trawlers switched from sail to steam-powered propulsion. These sea fisheries harvested all age-classes of sturgeons year-round, including populations from other European rivers. The outcomes strongly suggest that NW-European sturgeon populations were initially impacted by intensive river fisheries, but especially by destruction of reproductive habitat, due to river regulation, and an intensified North Sea fishery, ultimately resulting in total population collapse.

Environmental requirements and heterogeneity of rheophilic fish nursery habitats in European lowland rivers: Current insights and future challenges - Twan Stoffers; Antonie D. Buijse; Johan A. J. Verreth; Leopold A. J. Nagelkerke (Fish and Fisheries, 2022)
The large‐scale degradation of riparian ecotones and of the connectivity between rivers and their floodplains has resulted in a drastic decline of rheophilic fish populations in European temperate lowland rivers. Recent river restoration projects have had variable success in effectively restoring these fish populations. Knowledge on nursery habitat requirements is considered essential for effective population restoration. However, a detailed understanding of the role of habitat heterogeneity in young‐of‐the‐year (YOY) fish population development is limited. Therefore, we carried out a synthesis of the available knowledge on nursery habitat requirements of rheophilic fish species found in European temperate lowland rivers (

Landscape level effects of invasive plants and animals on water infiltration through Hawaiian tropical forests - Lucas Berio Fortini; Christina R. Leopold; Kim S. Perkins; Oliver A. Chadwick; Stephanie G. Yelenik; James D. Jacobi; Kai’ena Bishaw; Makani Gregg (Biological Invasions, 2021)

Sex differentiation in seasonal distribution of the starry smooth‐hound Mustelus asterias - Niels W. P. Brevé; Hendrik V. Winter; Paul A. D. M. Wijmans; Eleanor S. I. Greenway; Leopold A. J. Nagelkerke (Journal of Fish Biology, 2020)
This mark‐recapture study of starry smooth‐hound Mustelus asterias tagged during the summer months near the Dutch coast demonstrates a large‐scale spatial sex differentiation in their circannual migration patterns and small‐scale spatial sex differentiation during summer. Overwintering occurs in the North Sea, English Channel and Bay of Biscay, with significantly more males in the Northern North Sea and more females in the Bay of Biscay. During summer, sheltered sea arms off the Dutch coast were almost exclusively used by adult females. In subsequent summers post‐release, both sexes were mostly confined to the Southern North Sea, suggesting philopatry.

Spatial organization of occipital white matter tracts in the common marmoset - Takaaki Kaneko; Hiromasa Takemura; Franco Pestilli; Afonso C. Silva; Frank Q. Ye; David A. Leopold (Brain Structure and Function, 2020)

Fantastic Wetlands and Where to Find Them: Modeling Rich Fen Distribution in New York State with Maxent - Patrick A. Raney; Donald J. Leopold (Wetlands, 2018)

Plastic ingestion by harbour porpoises Phocoena phocoena in the Netherlands: Establishing a standardised method - Jan A. van Franeker; Elisa L. Bravo Rebolledo; Eileen Hesse; Lonneke L. IJsseldijk; Susanne Kühn; Mardik Leopold; Lara Mielke (Ambio, 2018)

Vulnerability of forests of the Midwest and Northeast United States to climate change - Chris Swanston; Leslie A. Brandt; Maria K. Janowiak; Stephen D. Handler; Patricia Butler-Leopold; Louis Iverson; Frank R. Thompson III; Todd A. Ontl; P. Danielle Shannon (Climatic Change, 2018)

Resilience of harbor porpoises to anthropogenic disturbance: Must they really feed continuously? - Jeroen P. A. Hoekendijk; Jerome Spitz; Andrew J. Read; Mardik F. Leopold; Michael C. Fontaine (Marine Mammal Science, 2018)

Priority effects are interactively regulated by top‐down and bottom‐up forces: evidence from wood decomposer communities - Devin R. Leopold; J. Paula Wilkie; Ian A. Dickie; Robert B. Allen; Peter K. Buchanan; Tadashi Fukami (Ecology Letters, 2017)
Both top‐down (grazing) and bottom‐up (resource availability) forces can determine the strength of priority effects, or the effects of species arrival history on the structure and function of ecological communities, but their combined influences remain unresolved. To test for such influences, we assembled experimental communities of wood‐decomposing fungi using a factorial manipulation of fungivore ( Folsomia candida ) presence, nitrogen availability, and fungal assembly history. We found interactive effects of all three factors on fungal species composition and wood decomposition 1 year after the fungi were introduced. The strength of priority effects on community structure was affected primarily by nitrogen availability, whereas the strength of priority effects on decomposition rate was interactively regulated by nitrogen and fungivores. These results demonstrate that top‐down and bottom‐up forces jointly determine how strongly assembly history affects community structure and function.

Localisation of keratin K78 in the basal layer and first suprabasal layers of stratified epithelia completes expression catalogue of type II keratins and provides new insights into sequential keratin expression - Lutz Langbein; Leopold Eckhart; Heinz Fischer; Michael A. Rogers; Silke Praetzel-Wunder; David A. D. Parry; Walter Kittstein; Juergen Schweizer (Cell and Tissue Research, 2016)

Glutamatergic markers, age, intellectual functioning and psychosis in 22q11 deletion syndrome - Laurens J. M. Evers; Therese A. M. J. van Amelsvoort; Jaap A. Bakker; Mariken de Koning; Marjan Drukker; Leopold M. G. Curfs (Psychopharmacology, 2015)

Trophic niche-space imaging, using resource and consumer traits - Leopold A. J. Nagelkerke; Axel G. Rossberg (Theoretical Ecology, 2014)

Characterizing Microclimate and Plant Community Variation in Wetlands - Patrick A. Raney; Jason D. Fridley; Donald J. Leopold (Wetlands, 2014)

Zooplankton, fish communities and the role of planktivory in nine Ethiopian lakes - Jacobus Vijverberg; Eshete Dejen; Abebe Getahun; Leopold A. J. Nagelkerke (Hydrobiologia, 2014)

Tumor necrosis factor-α-mediated suppression of dual-specificity phosphatase 4: crosstalk between NFκB and MAPK regulates endothelial cell survival - Derrick D. Kao; Scott R. Oldebeken; Anjali Rai; Edith Lubos; Jane A. Leopold; Joseph Loscalzo; Diane E. Handy (Molecular and Cellular Biochemistry, 2013)

Improving Wetland Mitigation Site Identification Through Community Distribution Modeling and a Patch-Based Ranking Scheme - Elizabeth A. Hunter; Patrick A. Raney; James P. Gibbs; Donald J. Leopold (Wetlands, 2012)

Expression of a Recombinant Extracellular Fragment of Human Vascular Endothelial Growth Factor Receptor VEGFR1 in E. coli - A. V. Leopold; V. P. Baklaushev; K. A. Pavlov; V. P. Chekhonin (Bulletin of Experimental Biology and Medicine, 2011)

Assessing the complex architecture of polygenic traits in diverged yeast populations - FRANCISCO A. CUBILLOS; ELEONORA BILLI; ENIKÖ ZÖRGÖ; LEOPOLD PARTS; PATRICK FARGIER; STIG OMHOLT; ANDERS BLOMBERG; JONAS WARRINGER; EDWARD J. LOUIS; GIANNI LITI (Molecular Ecology, 2011)
Phenotypic variation arising from populations adapting to different niches has a complex underlying genetic architecture. A major challenge in modern biology is to identify the causative variants driving phenotypic variation. Recently, the baker’s yeast, Saccharomyces cerevisiae has emerged as a powerful model for dissecting complex traits. However, past studies using a laboratory strain were unable to reveal the complete architecture of polygenic traits. Here, we present a linkage study using 576 recombinant strains obtained from crosses of isolates representative of the major lineages. The meiotic recombinational landscape appears largely conserved between populations; however, strain‐specific hotspots were also detected. Quantitative measurements of growth in 23 distinct ecologically relevant environments show that our recombinant population recapitulates most of the standing phenotypic variation described in the species. Linkage analysis detected an average of 6.3 distinct QTLs for each condition tested in all crosses, explaining on average 39% of the phenotypic variation. The QTLs detected are not constrained to a small number of loci, and the majority are specific to a single cross‐combination and to a specific environment. Moreover, crosses between strains of similar phenotypes generate greater variation in the offspring, suggesting the presence of many antagonistic alleles and epistatic interactions. We found that subtelomeric regions play a key role in defining individual quantitative variation, emphasizing the importance of the adaptive nature of these regions in natural populations. This set of recombinant strains is a powerful tool for investigating the complex architecture of polygenic traits.

Reciprocal regulation of 11β-hydroxysteroid dehydrogenase 1 and glucocorticoid receptor expression by dexamethasone inhibits human coronary artery smooth muscle cell proliferation in vitro - George Michas; Marcel Liberman; Kristian C. Becker; Diane E. Handy; Joseph Loscalzo; Jane A. Leopold (Molecular and Cellular Biochemistry, 2011)

Water-level regulation and coastal wetland vegetation in the upper St. Lawrence River: inferences from historical aerial imagery, seed banks, and Typha dynamics - John M. Farrell; Brent A. Murry; Donald J. Leopold; Alison Halpern; Molly Beland Rippke; Kevin S. Godwin; Sasha D. Hafner (Hydrobiologia, 2010)

Growth, biomass, and production of two small barbs (Barbus humilis and B. tanapelagius, Cyprinidae) and their role in the food web of Lake Tana (Ethiopia) - Eshete Dejen; Jacobus Vijverberg; Leopold A. J. Nagelkerke; Ferdinand A. Sibbing (Hydrobiologia, 2009)

Utilization of seagrass habitats by juvenile groupers and snappers in Banten Bay, Banten Province, Indonesia - Siti Nuraini; Eira C. Carballo; Wim L. T. van Densen; Marcel A. M. Machiels; Han J. Lindeboom; Leopold A. J. Nagelkerke (Hydrobiologia, 2007)

Serial Correlation and Inter-annual Variability in Relation to the Statistical Power of Monitoring Schemes to Detect Trends in Fish Populations - Leopold A. J. Nagelkerke; Wim L. T. van Densen (Environmental Monitoring and Assessment, 2007)

Extant and potential vegetation of an old-growth maritime Ilex opaca forest - Jodi A. Forrester; Donald J. Leopold (Plant Ecology, 2006)

Case Study Part 2: Probabilistic Modelling of Long-term Effects of Pesticides on Individual Breeding Success in Birds and Mammals - W. ROELOFS; D.R. CROCKER; R.F. SHORE; D.R.J. MOORE; G.C. SMITH; H.R. AKCAKAYA; R.S. BENNETT; P.F. CHAPMAN; M. CLOOK; M. CRANE; I.C. DEWHURST; P.J. EDWARDS; et al. (Ecotoxicology, 2005)

Case Study Part 1: How to Calculate Appropriate Deterministic Long-Term Toxicity to Exposure Ratios (TERs) for Birds and Mammals - R.F. SHORE; D.R. CROCKER; H.R. AKCAKAYA; R.S. BENNETT; P.F. CHAPMAN; M. CLOOK; M. CRANE; I.C. DEWHURST; P.J. EDWARDS; A. FAIRBROTHER; S. FERSON; D. FISCHER; et al. (Ecotoxicology, 2005)

A New Interpretation of Avian and Mammalian Reproduction Toxicity Test Data in Ecological Risk Assessment - Richard S. Bennett; I.C. Dewhurst; A. Fairbrother; A.D.M. Hart; M.J. Hooper; A. Leopold; P. Mineau; S.R. Mortensen; R.F. Shore; T.A. Springer (Ecotoxicology, 2005)

Visual processing in the ketamine-anesthetized monkey - David A. Leopold; Holger K. Plettenberg; Nikos K. Logothetis (Experimental Brain Research, 2002)

Microsaccades differentially modulate neural activity in the striate and extrastriate visual cortex - D. A. Leopold; Nikos K. Logothetis (Experimental Brain Research, 1998)

Multiple synchronization strategies in rhythmic sensorimotor tasks: phase vs period correction - Michael H. Thaut; Robert A. Miller; Leopold M. Schauer (Biological Cybernetics, 1998)